A REVIEW ON ASSESSMENT OF ARTEMISININ PRODUCTION UNDER ABIOTIC STRESS (International Journal of Food and Nutritional Sciences, 2022)
Recently, the growth of the world's population, the loss of arable land, soil erosion and conversion of agricultural land into urban area due to uncontrolled development have all put pressure on crop productivity. Artemisia annua is an annual plant native to Asia and Eastern Europe is the primary source of the antimalarial chemical compound artemisinin and it is a sesquiterpene alkaloid found in maximum amounts in the leaves. Although the extracted artemisinin content of A. annua is very low (dry weight approximately 0.01 to 1%). The plant stress such as temperature extremes, drought, alkalinity or salinity, UV radiation, and heavy metal have a negative impact on growth and development of plant. The techniques and time in which it is planted and harvested, as well as the weather circumstances, might have an influence on its productivity. However, the abiotic stress factors are utilized in in-vitro conditions to enhance production of artemisinin and other secondary metabolites by regulating the stress genes. The DBR2 gene has been demonstrated to induce a large increase in the amount of artemisinin made in A. annua, which is beneficial to the plant. Elicitation is a technique that has been used a lot in plant cell culture to make more secondary metabolites. This review elaborates the role of different abiotic factors on the production of artemisinin and the plant itself.